2010
DOI: 10.1016/j.bmcl.2010.07.103
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel in silico high-throughput screen to identify selective inhibitors for protein–protein interactions

Abstract: Increasing numbers of target protein structures available for computational studies makes the structure-based screening paradigm more attractive for initial hit indentification. We have developed a novel in silico screening methodology incorporating Molecular Mechanics (MM)/ implicit solvent methods to evaluate binding free energies and applied this technology to the identification of inhibitors of the TLR4/MD-2 interaction.* Corresponding author. Tel.: +1 303 492 6786; fax: +1 303 492 5894, hang.yin@colorado.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 31 publications
(25 reference statements)
0
30
0
Order By: Relevance
“…23 Energetically, it is a challenging goal to compete with two protein binding partners and block their association with small molecule agents. 15,41,42 The micromolar inhibitory activities observed with the β-amino alcohol derivatives render a promising starting point for further drug development optimization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Energetically, it is a challenging goal to compete with two protein binding partners and block their association with small molecule agents. 15,41,42 The micromolar inhibitory activities observed with the β-amino alcohol derivatives render a promising starting point for further drug development optimization.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 These inhibitors were shown to be effective at suppressing NF-κB activation in TLR4-overexpressing Human Embryonic Kidney (HEK) 293. 22 Herein, we further these studies on the preparation, optimization, and biological evaluation of β-amino alcohol derivatives that inhibit LPS-induced inflammation in whole blood.…”
Section: Introductionmentioning
confidence: 99%
“…Both bio-based and in silico- based experiments have shown that opioids could activate TLR4 on glial cells [25] . Their activation could result in the synthesis of nociceptive cytokines, which might exacerbate neuropathic pain and counteract the analgesic effects of opioids [26] .…”
Section: Tlr4-mediated Neuroinflammationmentioning
confidence: 99%
“…One of the early results of this effort is the crystal and solution structures of the UreA subunit, Rv1848, under PDB code 2FVH 34 . While UreA contains no known enzymatic function, it remains an appealing drug target within the emerging field of protein-protein interaction (PPI) inhibitors 35 .…”
Section: Solution and Crystal Structures Of Mtb Urea - The Implicatiomentioning
confidence: 99%